Relationship between clinical trials and disease burden of India: A cross-sectional study - Rimplejeet Kaur; Jaykaran Charan; Tea Reljic; Surjit Singh; Pankaj Bhardwaj; Athanasios Tsalatsanis; Ambuj Kumar (Journal of Pharmacy and Bioallied Sciences, 2020)
Background: Research output/efforts in a country should be reflective of the disease burden. India is a site for several national and multinational clinical trials. However, whether clinical trials performed in India reflect the disease burden is not well known. Objectives: The aim of this study was to evaluate the relationship between disease burden and clinical trials performed in India. Materials and Methods: We extracted data on the disease burden from the World Health Organization (WHO) website and on characteristics of clinical trials performed in India from the Clinical Trial Registry of India (CRTI). The correlation between disease burden parameters of overall mortality, disability-adjusted life years (DALYs), years lost due to disability (YLD) and years of life lost (YLL), and the frequency of clinical trials associated with a particular disease was assessed. Additional subgroup analysis according to the number of trial centers, study phase, and medicine type was also performed. Results: Only 18% of clinical trials addressed top 10 diseases associated with 68.3% of overall mortality, and 8% of clinical trials addressed top 10 diseases associated with 52.3% of DALYs. Similarly, 16% of clinical trials addressed top 10 diseases associated with 53.2% YLDs. Furthermore, top 10 diseases associated with 65.9% of YLLs were addressed in only 8% of ongoing clinical trials. The overall correlation between any disease burden parameters with the diseases being explored in clinical trials was poor. Conclusion: There is a mismatch between diseases for which clinical trials are happening in the India and the disease burden of India. Measures need to be taken to fulfill this gap between demand and need.